The effect of stem cells on alveolar bone remodeling during orthodontic tooth movement: Pengaruh sel punca terhadap proses remodelling tulang alveolar selama pergerakan gigi ortodontik - Ardiansyah S. Pawinru; Nurul Sakinah (Makassar Dental Journal PDGI Makassar, 2026)
Orthodontic tooth movement occurs through the application of mechanical forces that trigger a controlled process of alveolar bone remodelling, involving a balance between resorption by osteoclasts and new bone formation by osteoblasts. Stem cells, particularly mesenchymal stem cells (MSCs) and haemato-poietic stem cells (HSCs), play an important role in this mechanism. MSCs function as osteoblast precursors on the traction side, responding to mechani-cal forces through signalling pathways such as Wnt/?-catenin and MAPK/ERK to enhance osteogenesis. Meanwhile, HSCs differentiate into osteoclasts on the pressure side under the influence of RANKL, facilitating bone resorption. The coordinated activity of these two types of stem cells supports stable and efficient tooth movement. A deep understanding of the role of stem cells is not only important for improving the effectiveness of orthodontic treatment, but al-so opens up opportunities for the development of safer regenerative therapies, such as the use of exosomes or conditioned medium MSCs to optimise cli-nical outcomes and minimise complications.